2012
DOI: 10.1155/2012/380902
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Status and Quality of Life in relation to the Metabolic Syndrome: Isfahan Cohort Study

Abstract: Objective. Current study was designed to investigate the association of metabolic syndrome (MetS) with depression, anxiety, psychological distress, and quality of life (QoL). Design. Two hundred and fifteen contributors with MetS and 253 participants without MetS were randomly selected from 2151 participants of Isfahan Cohort Study who were residents of Isfahan city. Measurements consisted of fasting blood samples, anthropometrics, and self-reported data of 12-item General Health Questionnaire, Hospital Anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 27 publications
3
30
2
1
Order By: Relevance
“…Previous research shows an association between prevalence of different risk factors for metabolic syndrome and lower HRQoL in patients with depression and anxiety (Roohafza et al, 2012). Both men and women with metabolic syndrome had lower HRQoL compared with controls without the metabolic syndrome in a non-disease specific population study (Frisman and Kristenson, 2009).…”
Section: Introductionmentioning
confidence: 86%
“…Previous research shows an association between prevalence of different risk factors for metabolic syndrome and lower HRQoL in patients with depression and anxiety (Roohafza et al, 2012). Both men and women with metabolic syndrome had lower HRQoL compared with controls without the metabolic syndrome in a non-disease specific population study (Frisman and Kristenson, 2009).…”
Section: Introductionmentioning
confidence: 86%
“…Different studies have reported a positive trend toward the association between the number of MetS components and depression in young and older adults. 5,10,[13][14][15] However, a significant association between MetS components and depressive symptoms has not been detected. 6,9 To the best of our knowledge, there have been no studies focusing on the moderating effect of increasing number of MetS components on the association between MetS and depressive symptoms in population-based studies including older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Chou et al (2014) found that psychosocial factors, such as self-efficacy, self-esteem, and social stigma were determinants of lower HRQoL in patients with schizophrenia. Research has also demonstrated a link between the presence of various risk factors for metabolic syndrome and lower HRQoL (Roohafza et al 2012). Other contributing factors that can be linked to lower HRQoL are side effects of second generation antipsychotics (Bebbington et al 2009), social isolation (Sibitz et al 2010), and a high BMI and waist circumference (Faulkner et al 2007).…”
Section: Quality Of Life and Health-related Quality Of Lifementioning
confidence: 99%